2015
DOI: 10.1111/iju.12711
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation on clinical outcomes of robot‐assisted radical prostatectomy between experienced open prostatic surgeons and novice open surgeons in a laparoscopically naïve center with a limited caseload

Abstract: Objectives: To compare perioperative, oncological and functional outcomes of robotassisted radical prostatectomy between experienced and novice open radical prostatectomy surgeons in a laparoscopically naïve center with a limited caseload. Methods: Six surgeons carried out robot-assisted radical prostatectomy in 154 patients, which were divided into the following three groups: group 1 (n = 90), including patients operated on by a surgeon with experience in both open radical prostatectomy and robot-assisted rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…PSM rates in pathological 2, 3, and total were 9.3%, 47% and 22%, respectively, which was comparable with the 4–23%, 29–50% and 6.5–32%, respectively, reported in a recent study . In addition, the present oncological outcomes are better than those of a Japanese initial series in which PSM rates in pathological 2, 3, and total were 10–21%, 44–78% and 19–27%, respectively (Table S1). The present study also showed the differential pattern of PSM between a mentor and new surgeons with a mentor.…”
Section: Discussionsupporting
confidence: 85%
“…PSM rates in pathological 2, 3, and total were 9.3%, 47% and 22%, respectively, which was comparable with the 4–23%, 29–50% and 6.5–32%, respectively, reported in a recent study . In addition, the present oncological outcomes are better than those of a Japanese initial series in which PSM rates in pathological 2, 3, and total were 10–21%, 44–78% and 19–27%, respectively (Table S1). The present study also showed the differential pattern of PSM between a mentor and new surgeons with a mentor.…”
Section: Discussionsupporting
confidence: 85%
“…There is hence an even larger need for the outcome of the present study to be highlighted in Japan. This study will help introduce a validated curriculum for robot‐assisted radical prostatectomy for young Japanese urologists where it has now been established that a majority of the young urologists will become robotic surgeons without enough experience of open surgery, with the main aim of balancing and training new surgeons in robotic urological surgery and ensuring strict surgical quality control …”
mentioning
confidence: 99%
“…From their retrospective analysis of RARP, Sumitomo et al. described that their own series of RARP offered satisfactory peri‐ and postoperative outcomes even for surgeons with little or no ORP experience under an experienced mentor's supervision . They also pointed out the need for more training and experience for novice ORP surgeons, so they can overcome the learning curve on their first series of RARP cases.…”
mentioning
confidence: 99%